A Controlled Trial of Mass Drug Administration to Interrupt Transmission of Multidrug-Resistant Falciparum Malaria in Cambodian Villages. (7th March 2018) - Tripura, Rupam; Peto, Thomas J; Chea, Nguon; Chan, Davoeung; Mukaka, Mavuto; Sirithiranont, Pasathorn; Dhorda, Mehul; Promnarate, Cholrawee; Imwong, Mallika; von Seidlein, Lorenz; Duanguppama, Jureeporn; Patumrat, Krittaya; et al.
Abstract : In Cambodian villages, 3-month mass drug administration with high coverage using dihydroartemisinin-piperaquine was safe and was followed by the absence of clinical Plasmodium falciparum cases for at least 1 year, despite the presence of multidrug-resistant parasites. Abstract: Background: The increase in multidrug-resistant Plasmodium falciparum in Southeast Asia suggests a need for acceleration of malaria elimination. We evaluated the effectiveness and safety of mass drug administration (MDA) to interrupt malaria transmission. Methods: Four malaria-endemic villages in western Cambodia were randomized to 3 rounds of MDA (a 3-day course of dihydroartemisinin with piperaquine-phosphate), administered either early in or at the end of the study period. Comprehensive malaria treatment records were collected during 2014–2017. Subclinical parasite prevalence was estimated by ultrasensitive quantitative polymerase chain reaction quarterly over 12 months. Results: MDA coverage with at least 1 complete round was 88% (1999/2268), ≥2 rounds 73% (1645/2268), and all 3 rounds 58% (1310/2268). Plasmodium falciparum incidence in intervention and control villages was similar over the 12 months prior to the study: 39 per 1000 person-years (PY) vs 45 per 1000 PY ( P = .50). The primary outcome, P. falciparum incidence in the 12 months after MDA, was lower in intervention villages (1.5/1000 PY vs 37.1/1000 PY; incidence rate ratio, 24.5 [95% confidence interval], 3.4–177; P = .002). Following MDA in 2016, there were no clinical falciparum malaria cases over 12 months (0/2044 PY) in all 4 villages. Plasmodium vivax prevalence decreased markedly in intervention villages following MDA but returned to approximately half the baseline prevalence by 12 months. No severe adverse events were attributed to treatment. Conclusions: Mass drug administrations achieved high coverage, were safe, and associated with the absence of clinical P. falciparum cases for at least 1 year. Clinical Trials Registration: NCT01872702.